Impact of body mass index on cancer development - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2008)
Purpose: To determine the impact of body mass index (BMI) on cancer in a hospital-based Turkish population. Patients and methods: The study group consisted of 2015 (1172 females: 423 pre- and 749 postmenopausal; and 843 males) patients with histologically proven cancer who applied to Marmara University Medical School, Medical Oncology Clinic. The control group included 305 healthy caregivers (192 females: 110 pre- and 82 postmenopausal; and 113 males). Results: Mean BMI of the patients with breast, ovarian and cervical carcinoma was significantly higher than that of the healthy female controls (p<0.001, 0.003, <0.001, respectively). Postmenopausal breast cancer patients had significantly higher BMI than postmenopausal female controls (odds ratio [OR] 1.3; 95% confidence interval [CI], 1.06-1.6; p=0.012), while this was not seen in premenopausal patients. When compared with controls obese postmenopausal female patients had 3.26-fold (95% CI 1.54-6.90) increased risk for breast cancer (p=0.002). Mean BMI of lung, stomach, esophagus, pancreas and head and neck carcinoma patients was significantly lower than that of the healthy controls. Female patients with lung and colorectal carcinoma had higher BMI than female controls. Conclusion: Elevated BMI might be a risk factor for breast cancer in postmenopausal women. Case-control studies may not show the actual association between BMI and cancers that present with pre-diagnosis weight loss and advanced stage.
Keywords: body mass index; breast cancer; malignant neoplasms; obesity; OBESITY; RISK; ASSOCIATION; MORTALITY; ADENOCARCINOMA; OVERWEIGHT; ESOPHAGUS; WEIGHT; HEALTH; MEN